Optimization of process parameters to improve dimensional accuracy of investment casting using Taguchi approach - Sangita N Bansode; Vikas M Phalle; Shankar S Mantha (Advances in Mechanical Engineering, 2019)
In this study, Taguchi method is used to investigate the effect of critical process parameters of investment casting on dimensional variations of thin walled, complex geometrical stainless steel component. A set of experiments have been conducted to calculate shrinkages which is a measure of dimensional variation. The process parameters considered here are number of ceramic coats, pouring time, pouring temperature, and casting cooling rate. The signal-to-noise ratio and analysis of variance are used to study the influence of these parameters on shrinkage. Optimized condition for reduced shrinkage deviation can be obtained by selecting lower number of ceramic coats, faster and laminar metal pouring, lower superheated metal temperature, and faster cooling rate. Analysis of variance reports that the number of ceramic coats is the most significant parameter with more than 80% contribution whereas other parameters are insignificant. Investigation results also indicate that constraint dimension (width) has 25%–27% higher dimensional variability than non-constraint dimensions (height) for the selected component.